Hormonal Axis in Malignancy - From Pathogenesis to Therapeutics: Insights from Modern Oncology and Ayurveda (AYUSHDHARA, 2025)
Hormonal regulation is central to cancer pathogenesis, influencing cell proliferation, apoptosis, angiogenesis, and immune surveillance. Dysregulation of endocrine axes-including hypothalamus-pituitary-gonadal (HPG), hypothalamus pituitary adrenal (HPA), hypothalamus-pituitary-thyroid (HPT), and pituitary–liver axes-drives hormone-sensitive malignancies such as breast, prostate, ovarian, thyroid, and liver cancers. Genetic, lifestyle, and environmental factors further modulate hormonal balance and cancer susceptibility. Ayurvedic principles provide a complementary framework, linking Dosha imbalance, Dhatu dushti, Srotorodha, ama accumulation, and Ojas kshaya to endocrine dysfunction. Therapeutic strategies include modern hormone-targeted agents (selective receptor modulators, aromatase inhibitors, androgen blockers, PI3K/mTOR/CDK4/6 inhibitors) and context-specific Ayurvedic herbs (Ashwagandha, Shatavari, Rasayanas), emphasizing careful monitoring in hormone-sensitive cancers. Integrating modern oncology with Ayurvedic approaches, along with lifestyle modification, may offer holistic strategies for the prevention and management of endocrine-responsive malignancies.